10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
Night shift work has been associated with adverse health effects, although findings remain inconsistent. This study aimed to analyze the association between night shift work and sleep quality, chronotype, cardiometabolic parameters, and behavioral factors among hospital workers. A cross-sectional study was conducted among 225 normoglycemic workers at Son Llàtzer University Hospital (Mallorca, Spain). Sociodemographic and occupational data were collected through a structured questionnaire. Physical activity was assessed using the International Physical Activity Questionnaire (IPAQ), adherence to Mediterranean diet with the 14-item PREDIMED tool, sleep quality with the Pittsburgh Sleep Quality Index (PSQI), and chronotype with the Morningness-Eveningness Questionnaire (MEQ). Clinical parameters, including fasting plasma glucose, lipid profile, blood pressure, body mass index (BMI), waist circumference, and cardiovascular risk, were obtained from standardized health assessments. Associations with night shift work were examined using bivariate analyses and general linear models adjusted for age, sex, BMI, and physical activity. Night shift work was not significantly associated with fasting plasma glucose, triglycerides, HDL cholesterol, sleep quality, or chronotype. Compared with day workers, night shift workers showed lower levels of total and LDL cholesterol, blood pressure, BMI, and waist circumference, lower smoking rates, lower cardiovascular risk, and higher physical activity levels. No significant differences were observed in adherence to the Mediterranean diet. After adjustment for age and sex, only the association between night shift work and physical activity remained significant. Overall, night shift work was not associated with poorer health status or increased cardiovascular risk. Instead, no consistent evidence of a less favourable lifestyle was observed among night shift workers.